EVALUASI PROGRAM PENGADAAN TRUK SAMPAH DI DESA PAKATTO BONTOMARANNU KABUPATEN GOWA - Muttahhara, Irmadana; Fatmawati, Fatmawati; Nasrulhaq, Nasrulhaq (Universitas Muhammadiyah Makassar, 2023)
This study purposed to find out the evaluation of the Garbage Truck Procurement Program in Pakatto Bontomarannu Village, Gowa Regency. The type of research used qualitative as an attempt to describe in general with the existing facts. There were 9 informants. The data collection techniques were Interview, Direct Observation and Documentation. The results showed that the effectiveness of the procurement of garbage trucks in Pakatto village was considered more effective for villagers considering the habit of residents/communities being more likely to throw their garbage around the river. The efficiency of this garbage truck procurement was considered very good, based on the community's regular monthly fee of Rp. 20,000. This routine fee was allocated for the operational costs of the garbage collectors for the BumDes cash inflow. The adequacy of the procurement of this garbage truck was considered sufficient in transporting the waste of residents who had paid their dues. The responsiveness of the community was different, there were people who responded quite well and there were also people who responded with uninterested. The accuracy of the garbage truck procurement program was considered inappropriate, considering the highland areas that could not be reached by garbage trucks and the principle of benefit was no longer appropriate for its function.Keywords: Evaluation and Truck Procurement Program